WEBSITE JOB SEARCH DEVELOPMENT: A CASE STUDY OF TOBA REGENCY - Hernawati Samosir; Pratiwi Sibarani; Diah Sirait; Sofhia Tambun; Michael S (Institute of Computer Science (IOCS), 2021)
The information and communication development technology continues relentlessly. Especially when it comes to knowledge, data plays a significant role. In this case, one of the services obtained from the internet is website access. There is a wide variety of information provided by the website, one of which is the job opening website. Many people searching for work have difficulty because the information provided by the concerned often makes applicants disappointed because of the delay in data that has not mentioned the number of requirements needed.This study explores user responses to website containing job openings in one particular Toba district. Designing a web-based job application using the PHP programming language and MySQL as the database became a solution for the problem. The application for a job search in Toba Regency itself has never existed. This application can simplify job seekers to find job vacancies information and the employers can add job vacancies. The application development model used is the waterfall method. We chose this method because this method provides sequential and systematic development steps in developing software. The waterfall stages used in this website consist of communication, planning, modeling, and construction.